2015
DOI: 10.1109/tdei.2015.7076826
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise electric field induced charging current and its correlation with space charge formation in LDPE/ZnO nanocomposite

Abstract: This study intends to establish the correlation between charging current under stepwise increased electric field and space charge formation in low density polyethylene (LDPE) and LDPE/ZnO nanocomposites. By applying stepwise increased electric field, the charging current and space charge distribution were measured as a function of time under 10, 30 and 50 kV/mm, respectively. The results show that homopolar space charge formation induces increasing charging current with time, while heteropolar space charge for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Space charge generates dissipative loss, reduces the withstand voltage, intensifies the local electric field and can produce insulation failure [37]. The addition of small volume fractions of nanofillers can reduce the space charge extent [8], [39], [40] this effect being especially notorious at low filler concentration [41], thus enhancing the volume resistivity. The tendency to suppress charge injection is believed to be due to deep trap mechanisms [42] that capture the charge injected by the electrodes, thus, reducing the electrical conduction [43] by inhibiting charge injection and avoiding space charge buildup.…”
Section: Dielectric Testsmentioning
confidence: 99%
“…Space charge generates dissipative loss, reduces the withstand voltage, intensifies the local electric field and can produce insulation failure [37]. The addition of small volume fractions of nanofillers can reduce the space charge extent [8], [39], [40] this effect being especially notorious at low filler concentration [41], thus enhancing the volume resistivity. The tendency to suppress charge injection is believed to be due to deep trap mechanisms [42] that capture the charge injected by the electrodes, thus, reducing the electrical conduction [43] by inhibiting charge injection and avoiding space charge buildup.…”
Section: Dielectric Testsmentioning
confidence: 99%
“…The formation and accumulation of space charges has become one of the major problems that urgently needs to be solved for the development of high voltage direct current (HVDC) cable polyethylene (PE) insulation materials. The space charges are formed by the transfer and storage of the charge carriers injection by the electrodes and the ionization of the impurities or additives such as antioxidants, etc., in the bulk of PE insulation materials, which could lead to local electric field distortion and the local field may be eight times more than the applied electric field especially when the polarity of the line is inverted [1,2,3,4]. The distortion of the electric field caused by space charge accumulation could affect the conduction, breakdown and ageing phenomena of PE insulation materials, and reduce the long-term reliability and service life of direct current (DC) cables [5].…”
Section: Introductionmentioning
confidence: 99%
“…Although low‐density polyethylene (LDPE) is considered the best candidate as insulation for HVDC cables due to its high breakdown strength and resistivity, the space charge accumulation in strong electric fields results in early failure in the cable insulations. The mobility of the space charge carriers in polymers is attributed to ionic conduction (impurity ionization) and electronic conduction (charge injection from electrodes) . Recently, it has been reported that space charge accumulation and electric conductivity reductions in LDPE insulation can be achieved by the addition of a low content (<5 wt%) of metal‐oxide nanoparticles.…”
mentioning
confidence: 99%
“…Recently, it has been reported that space charge accumulation and electric conductivity reductions in LDPE insulation can be achieved by the addition of a low content (<5 wt%) of metal‐oxide nanoparticles. These, being either insulating (Al 2 O 3 , MgO, and SiO 2 ) or semiconducting (TiO 2 and ZnO), have a higher conductivity than that of the LDPE matrix, and they reduce the charge mobility in the LDPE nanocomposites through trapping/adsorption of charge carriers, including electrons, holes, and polar/ionic species . The final electrical properties of the nanocomposites depend on the degree of particle dispersion, size, morphology, and crystal surfaces of the incorporated nanoparticles.…”
mentioning
confidence: 99%